2020
DOI: 10.1055/s-0040-1710009
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Shirodkar Cerclage and Preterm Premature Rupture of Membranes in Singleton Pregnancies

Abstract: Objective The aim of this study was to estimate if preterm premature rupture of membranes in women with cerclage is due to the cerclage itself or rather the underlying risk factors for preterm birth in this population. Study Design This was a retrospective cohort study of singleton pregnancies who underwent Shirodkar cerclage by a single maternal–fetal medicine practice between 2005 and 2019. The control group was an equal number of randomly selected women with a singleton gestation who had a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the study conducted by Liu et al, PPROM complicated 30% and 39% of pregnancies after prophylactic and therapeutic cerclage, respectively [ 11 ]. However, a recent study by Muniz Rodriguez et al found that all three types of cerclage procedures did not increase the risk of PPROM before 34 weeks when compared with pregnancies at increased risk for preterm birth [ 15 ]. They also attributed higher rates of PPROM reported previously among patients with cerclage to significant baseline risk for preterm birth due to dilated or short cervix, prior history of preterm birth or PPROM and prior cerclage.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Liu et al, PPROM complicated 30% and 39% of pregnancies after prophylactic and therapeutic cerclage, respectively [ 11 ]. However, a recent study by Muniz Rodriguez et al found that all three types of cerclage procedures did not increase the risk of PPROM before 34 weeks when compared with pregnancies at increased risk for preterm birth [ 15 ]. They also attributed higher rates of PPROM reported previously among patients with cerclage to significant baseline risk for preterm birth due to dilated or short cervix, prior history of preterm birth or PPROM and prior cerclage.…”
Section: Discussionmentioning
confidence: 99%
“…However, women undergoing cerclage placement remain at high risk for preterm labor and preterm prelabor rupture of membranes (PPROMs). Although cerclage does not seem to increase the risk of PPROM compared with other women at increased risk of preterm birth, there is an association between cerclage placement and PPROM likely due to underlying risk factors 3 . PPROM is strongly associated with maternal, fetal, and neonatal morbidity and mortality due to increased risk of infection, oligohydramnios, and prematurity 4 .…”
mentioning
confidence: 99%